A Study on the Role of Guanxi Networks on Job Search in A China’s Second Tier City: Yuncheng - Zhao, Pengyao (2012)
There has been considerable research concerning the concept of Guanxi on its different aspects. This dissertation will only focus on one aspect of Guanxi: its role on the job search process. Using a China’s second tier city as a case study, this study will explore the role of Guanxi networks on job search in Yuncheng, The research method used in this study is qualitative approach. The research findings derived from semi-structured interviews with 20 respondents selected from Yuncheng. The main finding of this research is that Guanxi networks are influential in Yuncheng even with the economic reform. Especially, it is found that interviewees’ fathers play a dominant role in the job search process. The study in Yuncheng also reveals that Guanxi is most influenced in searching jobs in the state sector.